Studi Komparatif dalam Pembentukan Karakter Siswa Dengan Model Pembelajaran Happy Note di Kelas 3 di SD 1 Barongan - Shallum, Geitsya Alodia; Mustovina, Nazly Maulidatul; Putri, Chindy Adelia Cantika; Fakhiriyah, Fina; Ismaya, Erik Aditia (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
The purpose of this study was to analyze the improvement of learning in elementary schools (SD) in the formation of student character in the subject of Natural and Social Sciences (IPAS) through a comparative quantitative approach (non-experimental). The method used is a comparative quantitative method. The subjects of the study consisted of students in grades 3A and 3B who used the same learning model, namely the happy note learning model (notes developed according to student creativity). Data collection techniques were based on teacher assessments of student character, observation, and documentation. Data analysis used a comparative statistical tests (t-tests) to determine significant differences in the results between students in grades 3A and 3B. The result showed significant differences in the formation of student character between the two classes. The average score of class 3A was 92,58 and class 3B was 97,97 with a sigificance value (p-value) of 0,000 (< 0,05) which indicates that the Happy Note learning model is effective in forming student character.